How Important of Students' Literacy and Numeracy Skills in Facing 21st-Century Challenges: A Systematic Literature Review - Deda, Yohanis Ndapa; Disnawati, Hermina; Daniel, Otaget (Indonesian Journal of Educational Research and Review, 2023)
Literacy Numeracy skills (LNS) are fundamental for facing global challenges in the 21st century. LNS can help people achieve their goals. However, there has not been a thorough study on literacy and numeracy research. To improve the quality of literacy and numeracy research, researchers must study much literature for further analysis. This research aims to analyze students' literacy and numeracy skills in facing 21st-century challenges. The research method used is the Systematic Literature Review to read 27 documents by searching for the keywords "literacy", "numeracy", and “Literacy and Numeracy”. This type of research is library research with the stages of determining research questions, searching literature, selecting articles, reading full papers, making abstractions, and conducting analysis. The data analysis technique used is content analysis. The study results show that the dominant research methodology used is quantitative; the instruments often used are tests and assessments. The chief field is mathematics; the overall educational level is junior high school and early childhood education. Some motivational results research related to literacy and numeracy skills includes digital competencies, learning videos, and games, effectively improving literacy and numeracy skills. Furthermore, not all learners have strong reading and numeracy abilities. A strong recommendation for further research is to develop learning media based on local wisdom using the Android platform. In addition, researchers must embed emergent literacy in the design and case study of didactically and pedagogically oriented research.